1028 nm single mode Ytterbium-doped fiber laser - Paul, Mukul Chandra; Harun, Sulaiman Wadi; Moghaddam, M.R.A.; Das, Sagnik; Sen, Ranjan; Dhar, Anirban; Pal, Mrinmay; Bhadra, Shyamal Kumar; Ahmad, Harith (IOP Publishing, 2009)
An efficient Ytterbium-doped fiber laser (YDFL) operating at 1028 nm is demonstrated using a fiber Bragg grating (FBG). The Ytterbium-doped fiber (YDF) is drawn from Yb2O3-doped preform, fabricated through deposition of porous layer of composition SiO2-GeO2 by the MCVD process in conjunction with a solution doping technique. The fabricated YDF has a 0.1 mol % of Yb2O3 in the core, a Ytterbium ion lifetime of 1.1 ms, an absorption of 7.65 dB/m at 976 nm. The fiber laser has the maximum efficiency of 51% with pump power threshold of 19 mW using a FBG in conjunction with a Fresnel reflection to form a linear cavity resonator. The efficiency and threshold are better compared to the similar YDFL configuration using a commercial YDF.